Binimetinib, pemetrexed and cisplatin, followed by maintenance of binimetinib and pemetrexed in patients with advanced non-small cell lung cancer (NSCLC) and KRAS mutations. The phase 1B SAKK 19/16 trial. (June 2021) - Froesch, Patrizia; Mark, Michael; Rothschild, Sacha I.; Li, Qiyu; Godar, Gilles; Rusterholz, Corinne; Oppliger Leibundgut, Elisabeth; Schmid, Sabine; Colombo, Ilaria; Metaxas, Yannis; König, David; Sessa, Cristiana; et al.
Highlights: Patients with KRAS-mutated (exon 2 or 3) treatment-naïve advanced NSCLC. Multicenter phase 1B trial with the MEK inhibitor Binimetinib in combination with cisplatin and pemetrexed. No unexpected adverse event in 16 patients evaluable for safety. No signal of increased efficacy with binimetinib at MTD (ORR = 33%), median PFS = 5.7 months, OS = 6.5 months). Abstract: Background: KRAS mutations are found in 20–25 % of non-squamous non-small cell lung cancer (NSCLC) and therapies targeting the RAS/MEK/ERK pathway are in development. We performed a multicenter open-label phase 1B trial to determine the recommended phase 2 dose and early antitumor activity of the MEK-inhibitor binimetinib combined with cisplatin and pemetrexed. Methods: Eligible patients (pts) had stage III-IV NSCLC unsuitable for curative treatment, KRAS exon 2 or 3 (codon 12, 13 or 61) mutations, no prior systemic therapy. Pts were enrolled into part 1: 3 + 3 design with dose escalation in 2 dose levels (DL) of binimetinib and part 2: expansion cohort at the maximum tolerated dose (MTD). Pts received 4 cycles of cisplatin 75 mg/m 2, pemetrexed 500 mg/m 2 and binimetinib 30 (DL1)/45 mg (DL2) orally twice a day (bid) d1–14 q3w followed by pemetrexed and binimetinib until progressive disease (PD) or unacceptable toxicity. Results: From May 2017 to Dec 2019, 18 pts (13 dose escalation, 5 expansion cohort) were enrolled. Median age was 60 (48–73, range). KRAS mutations were 87.5 % at codon 12. No DLT occurred in the dose escalation cohort. Median number of cycles was 2 (1–17, range). Treatment discontinuation was mainly due to PD (33 %) or pts/physicians' decision (27 %). Together with the expansion cohort, 16 pts were evaluable for safety. Most frequent treatment-related grade 3 AEs were lung infection (25 %), fatigue (19 %), anemia (19 %). Overall response rate among 9 evaluable pts receiving binimetinib at MTD (45 mg bid) was 33 % (7–70 %, 95 % CI). Median progression-free survival was 5.7 months (1.1−14.0, 95 % CI) and overall survival 6.5 months (1.8-NR, 95 % CI). Conclusions: Pts treated with combination of cisplatin, pemetrexed and binimetinib presented no unexpected toxicity. No early signal of increased antitumor activity of binimetinib added to chemotherapy was observed in our pts population.